Impact of Energy Consumption on Industrial Sector Performance - Ogochukwu Christiana Anyanwu; Keghter Kelvin Kur (SAGE Open)
In order to stimulate economic growth, most African countries have engaged the industrial sector to reduce their dependence on importation. This prompted the need for this study to investigate the impact of energy consumption on industrial performance. The study utilized panel data across 32 Sub Saharan African countries from 2002 to 2019. The Fully Modified Ordinary Least Squares (FMOLS), Pooled Mean Group (PMG) and Generalized Linear Model (GLM) techniques were employed to evaluate the long-term impacts. To ensure an in-depth study, the paper focused on two groups of countries; the lower-middle-income and low income countries and merged them into a single group. The major findings from the study is the positive associations between energy consumption, renewable energy consumption and fossil fuel consumption on industrial sector performance. This means that increased energy consumption enhances the productive capacities of industries, which steers economic growth across the region. Further findings revealed a negative association between foreign direct investment and industrial sector performance. The study recommended the usage of clean energy since increased energy consumption in form of fossil fuels influences climate change.